Primary Mouse Choroidal Endothelial Cell Culture - Qiuhua Yang; Yongfeng Cai; Qian Ma; Yuqing Huo (Bio-Protocol, 2025)
The study of choroidal endothelial cells is essential for understanding the pathological mechanisms underlying choroidal neovascularization and other vision-threatening disorders. Traditional methods for isolating and culturing primary endothelial cells often yield mixed populations or require specialized equipment, limiting their widespread use. Here, we present a straightforward protocol for isolating and culturing primary mouse choroidal endothelial cells. This protocol involves enzymatic digestion of choroidal tissue, magnetic-activated cell sorting (MACS) to enrich CD31+ endothelial cells, and optimized culture conditions to promote cell proliferation and maintain endothelial phenotype. The protocol is strategic, reproducible, and requires minimal specialized equipment, making it accessible for researchers across various fields. By providing a robust method for obtaining pure choroidal endothelial cell cultures, this protocol facilitates the study of cell-specific behaviors and responses, advancing research into choroidal vascular diseases.